http://isrctn.com/ 2020
DOI: 10.1186/isrctn66774780
|View full text |Cite
|
Sign up to set email alerts
|

Size and shape of plates and size of wine glasses and bottles: impact on selection of food and alcohol

Abstract: Background:The physical properties of tableware could influence selection and consumption of food and alcohol. There is considerable uncertainty, however, around the potential effects of different sizes and shapes of tableware on how much food and alcohol people self-serve. These studies aimed to estimate the impact of: 1. Plate size and shape on amount of food self-served; 2.Wine glass and bottle size on amount of wine self-poured.Methods: 140 adults participated in two laboratory studies-each using randomise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
(22 reference statements)
1
2
0
Order By: Relevance
“…The current study did not find evidence for an interaction between bottle size and glass. This is consistent with the findings of the aforementioned laboratory study, which found no significant interaction effect when participants were asked to pour wine into differently sized glasses from differently sized bottles [21]. The effects might, however, be different when multiple servings are permitted and poured amounts are consumed, as was the case with the current study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The current study did not find evidence for an interaction between bottle size and glass. This is consistent with the findings of the aforementioned laboratory study, which found no significant interaction effect when participants were asked to pour wine into differently sized glasses from differently sized bottles [21]. The effects might, however, be different when multiple servings are permitted and poured amounts are consumed, as was the case with the current study.…”
Section: Discussionsupporting
confidence: 93%
“…A recent mega-analysis found that wine served in larger glasses increased the volume of wine sold, and therefore consumed, in restaurants but not in bars [20]. Consistent with this, a recent laboratory study found that less wine was poured into smaller glasses compared to larger glasses [21], suggesting that smaller glasses might reduce consumption by reducing amounts that are self-poured.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation